Early Ultrafiltration Therapy in a Patient with Decompansated Heart Failure and Acute Pulmonary Edema in the Setting of Diuretic Resistance (Annals of Medical Research, 2021)
None
Keywords: Congestive heart failure, Diuretic resistance, Ultrafiltration